Selective memory Test: memory system changes that occur through the time. An exploratory study - Sarriá J., César (2006)
Is knowned that amnesiac process is one of more important areas of de neuropsychological exploration and many investigators have made explicative propositions about amnesiac disorders. The present study present normative dates that are a consequence of people in that age.